2020
DOI: 10.3389/fneur.2020.00810
|View full text |Cite
|
Sign up to set email alerts
|

Identifying a Comprehensive ceRNA Network to Reveal Novel Targets for the Pathogenesis of Parkinson's Disease

Abstract: Parkinson's disease (PD) is the second commonest progressive neurodegenerative disease worldwide. Increasing evidence reveals that non-coding RNAs play roles in the pathophysiological process of PD. The notion called competing endogenous RNAs (ceRNAs) network is used to describe the roles of non-coding RNAs. According to this theory, long non-coding RNAs (lncRNAs) act as microRNAs (miRNAs) sponges by miRNA response elements or miRNA binding sites to control the availability of endogenous miRNA for binding to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 34 publications
(37 reference statements)
0
13
0
Order By: Relevance
“…This network consisted of 7 lncRNAs (including XIST, PART1, MCF2L2, NOP14-AS1, LINC00328, LINC00302 and FAM215A), 3 miRNAs (miR-7, miR-133b and miR-433) and 55 mRNAs especially enriched in the GnRH, insulin and MAPK signaling pathways. More recently, Zhang and colleagues [ 113 ] identified a new network in a substantia nigra array from PD patients and matched healthy controls that comprised 9 lncRNAs, 18 miRNAs, and 185 mRNAs functionally related to autophagy, DNA repair and vesicle transport, all critical cellular processes in PD. Based on the most significant relationships, they established a second ceRNA network that was validated using external data.…”
Section: Cerna Network and Neurodegenerative Diseasesmentioning
confidence: 99%
“…This network consisted of 7 lncRNAs (including XIST, PART1, MCF2L2, NOP14-AS1, LINC00328, LINC00302 and FAM215A), 3 miRNAs (miR-7, miR-133b and miR-433) and 55 mRNAs especially enriched in the GnRH, insulin and MAPK signaling pathways. More recently, Zhang and colleagues [ 113 ] identified a new network in a substantia nigra array from PD patients and matched healthy controls that comprised 9 lncRNAs, 18 miRNAs, and 185 mRNAs functionally related to autophagy, DNA repair and vesicle transport, all critical cellular processes in PD. Based on the most significant relationships, they established a second ceRNA network that was validated using external data.…”
Section: Cerna Network and Neurodegenerative Diseasesmentioning
confidence: 99%
“…In addition, accumulated studies have been shown that FBXL7 regulates various biological processes, including apoptosis [ 16 , 18 , 20 ], proliferation [ 16 , 21 , 22 ], mitochondrial function [ 20 ], epithelial-mesenchymal transition (EMT) [ 23 , 24 ], glucose metabolism [ 25 ], DNA damage [ 26 ], endothelial function [ 27 ], allergic inflammatory response [ 28 , 29 ], embryonic development [ 30 ], planar cell polarity [ 31 , 32 ], and drug resistance [ 33 – 35 ]. Therefore, FBXL7 is involved in various human diseases, including asthma [ 28 , 29 , 36 , 37 ], atopy [ 38 ], Alzheimer’s disease [ 39 ], acute urticaria/angioedema [ 40 ], rheumatoid arthritis [ 41 ], Parkinson’s disease [ 42 ], chronic obstructive pulmonary disease [ 26 ], form-deprivation myopia [ 43 ], and cancer [ 23 , 24 , 35 ]. In this review, we summarize the downstream substrates and upstream regulators of FBXL7 and describe its aberrant expression in human cancers, with emphasis on its emerging roles in the regulation of tumorigenesis and tumor progression.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the inhibitory effect of miRNA on mRNA might be canceled when miRNAs is combined with MRE on lncRNA. Recently, accumulating studies have demonstrated that the ceRNA network has become increasingly important in the occurrence and progression of diverse diseases, including cancers, Parkinson’s disease, myocardial ischemia/reperfusion injury, and cerebral infarction ( Zou et al, 2019 ; Qi et al, 2020 ; Zhang R. et al, 2020 ; Zhang X. et al, 2020 ). Nonetheless, few studies of ceRNA network in SCII have been reported ( Liu et al, 2018 ; Qiao et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%